Influence of the non-metal species on the oxidation kinetics of Hf, HfN, HfC, and HfB2 coatings. (1st December 2021) - Glechner, T.; Hudak, O.E.; Wojcik, T.; Haager, L.; Bohrn, F.; Hutter, H.; Hunold, O.; Ramm, J.; Kolozsvári, S.; Pitthan, E.; Primetzhofer, D.; Riedl, H.
Graphical abstract: Highlights: Broad variation of oxidation kinetics for Hf, HfC0.96, HfN1.5 and HfB2.3 coatings. Hf, HfC0.96, HfN1.5 and HfB2.3 coatings exhibit different oxide scale morphologies. Comparable oxidation resistance of HfN1.5 and HfB2.3 coatings. Exceptional low oxygen inward diffusion for HfB2.3 coatings at 900 °C. Study highlights the impact of the non-metal species on the oxidation resistance. Abstract: The influence of the non-metal species on the oxidation resistance of transition metal ceramic based thin films is still unclear. For this purpose, we thoroughly investigated the oxide scale formation of a metal (Hf), carbide (HfC0.96 ), nitride (HfN1.5 ), and boride (HfB2.3 ) coating grown by physical vapor deposition. The non-metal species decisively affect the onset temperature of oxidation, ranging between 550 °C for HfC0.96 to 840 °C for HfN1.5 . HfB2.3 and HfN1.5 obtain the slowest oxide scale kinetic following a parabolic law with kp values of 4.97∙10 -10 and 5.66∙10 -11 kg 2  m -4  s −1 at 840 °C, respectively. A characteristic feature for the oxide scale on Hf coatings, is a columnar morphology and a substantial oxygen inward diffusion. HfC0.96 reveals an ineffective oxycarbide based scale, whereas HfN1.5 features a scale with globular HfO2 grains. HfB2.3 exhibits a layered scale with a porous boron rich region on top, followed by a highly dense and crystalline HfO2 beneath. Furthermore, HfB2.3 presents a hardness of 47.7 ± 2.7 GPa next to an exceptional low inward diffusion of oxygen during oxidation. This study showcases the strong influence of the non-metallic bonding partner despite the same metallic basis, as well as the huge potential for HfB2 based coatings also for oxidative environments.